2013 Asilomar Conference on Signals, Systems and Computers 2013
DOI: 10.1109/acssc.2013.6810573
|View full text |Cite
|
Sign up to set email alerts
|

Full-duplex in large-scale wireless systems

Abstract: In this paper, we investigate the combination of fullduplex wireless communication with large-scale multiple-input multiple-output (MIMO) technology, which has the potential for bidirectional wireless communication at high spectral efficiency and low power consumption. In addition, we study its application to cellular (multi-user) systems that could be extended with large antenna arrays, such as 3GPP LTE. In order to solve the fundamental issue of self-interference cancellation in fullduplex cellular communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 17 publications
0
74
0
Order By: Relevance
“…This trend is in line with recent major advances in SI supression techniques [10]- [12]. Broadly speaking, SI can be tackled using isolation in space [13], [14], digital/analog subtraction [15], [16], and as a combination of both [17]. Several real-time point-to-point prototypes of FD radio nodes have been demonstrated in practice recently [18].…”
Section: Introductionmentioning
confidence: 67%
“…This trend is in line with recent major advances in SI supression techniques [10]- [12]. Broadly speaking, SI can be tackled using isolation in space [13], [14], digital/analog subtraction [15], [16], and as a combination of both [17]. Several real-time point-to-point prototypes of FD radio nodes have been demonstrated in practice recently [18].…”
Section: Introductionmentioning
confidence: 67%
“…In order to simplify the derivations, the interference caused by uplink transmission to downlink MSs was ignored in [14] and [15]. On the other hand, the interference caused by uplink transmission to downlink MSs is considered in [16]- [19].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the proposed alignment-based precoder differs from the extended ZF scheme in [10] and subsequent works where 'allzero' streams are transmitted for SI cancellation purposes. In addition, the linear ZF decoder at the l-th BS, which eliminates multi-user interference in the UL, is constructed with the normalized rows of H…”
Section: Baseband Signals Representationsmentioning
confidence: 99%
“…For example, the authors in [9] have shown that the FD functionality in the context of baseline single-input single-output (SISO) cellular networks can result in the doubling of the DL rate at the cost of over a thousand-fold deduction in the UL rate. A potential solution can be to exploit massive MIMO for better resilience against SI and cross-mode interference as highlighted in [10] and [11], which focus on a single-cell LSAS scenario.…”
Section: Introductionmentioning
confidence: 99%